1982
DOI: 10.1175/1520-0477-63.5.503
|View full text |Cite
|
Sign up to set email alerts
|

Possible Triggering Mechanisms for Severe Storms in SESAME-AVE IV (9–10 May 1979)

Abstract: The SESAME-AVE IV (9-10 May 1979) rawinsonde data were analyzed to uncover possible triggering mechanisms for severe storms that developed over western Oklahoma and Texas. The high frequency of observations (at 3 h intervals) and high vertical resolution of reported data (at 25 mb intervals) at all stations permitted investigation of the diurnal variation of the planetary boundary layer on the synoptic scale. Thunderstorms developed first just ahead of a stationary front over the Texas panhandle on the afterno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Near the dryline boundary, severe thunderstorms are often triggered during the premonsoon (Weston, 1972;Akter and Ishikawa, 2014). However, upward motions occur in the dry air to the west of the dryline, offsetting the formation of convection in the moist air to the east of the dryline, as noted in previous studies (Koch and McCarthy, 1982;Ogura et al, 1982). Further studies using higher resolution numerical model are necessary to understand the triggering mechanisms of the convection and to help identify the differences between convection on the western and eastern sides of the dryline.…”
Section: Discussionmentioning
confidence: 80%
“…Near the dryline boundary, severe thunderstorms are often triggered during the premonsoon (Weston, 1972;Akter and Ishikawa, 2014). However, upward motions occur in the dry air to the west of the dryline, offsetting the formation of convection in the moist air to the east of the dryline, as noted in previous studies (Koch and McCarthy, 1982;Ogura et al, 1982). Further studies using higher resolution numerical model are necessary to understand the triggering mechanisms of the convection and to help identify the differences between convection on the western and eastern sides of the dryline.…”
Section: Discussionmentioning
confidence: 80%
“…This sharp meridional moisture gradient in close proximity to the genesis region of southern Niger has a diurnal cycle analogous to drylines observed over the south-central Great Plains of the U.S. (Schaefer 1986). While thunderstorms tend to develop in their vicinity, drylines are not the triggering mechanism for convection (e.g., Ogura et al 1982;Carlson et al 1983;Trier et al 2015). However, the dryline's proximity can be an important environmental factor because convective systems that form near them tend to become stronger and better organized (Rhea 1966).…”
Section: Conditions For Mcss With Daytime Genesis <1000 Km Away From mentioning
confidence: 99%
“…While drylines are typically associated with atmospheric conditions favorable for the development of convection, it does not necessarily mean that it is the triggering mechanism (Ogura et al 1982;Carlson et al 1983;Benjamin and Carlson 1986). As discussed in the above-mentioned studies, the primary role of the dryline is to provide a restraining inversion for lower-tropospheric turbulence that suppresses the release of convective instability too early in the day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…parent surface frontal feature, but is collocated with the leading edge aloft of a forward-tilted eastward-moving Pacific cold front. Many studies have shown that convection can be initiated when a cold front overtakes a dryline, or lee trough (Koch and McCarthy 1982;Ogura et al 1982;Shapiro 1982;Schaefer 1986;Neiman et al 1998;Neiman and Wakimoto 1999;Stoelinga et al 2000). However, in cases where the cold front proceeds aloft after overtaking a lee trough, and an extensive squall line develops and remains collocated with the CFA, the dynamical role of the CFA in maintaining the squall line, rather than just initiating it, has not been well established.…”
Section: Volume 131 M O N T H L Y W E a T H E R R E V I E Wmentioning
confidence: 99%